2022
DOI: 10.1002/ps.7232
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of rosin‐based acylhydrazone derivatives as potential antifungal agents against rice Rhizoctonia solani for sustainable crop protection

Abstract: BACKGROUND The use of fungicides to protect crops from diseases is an effective method, and novel environmentally friendly plant‐derived fungicides with enhanced performance and low toxicity are urgent requirements for sustainable agriculture. RESULTS Two kinds of rosin‐based acylhydrazone compounds were designed and prepared. Based on the antifungal activity assessment against Rhizoctonia solani, Fusarium oxysporum, Phytophthora capsici, Sclerotinia sclerotiorum, and Botrytis cinerea, acylhydrazone derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…8 Therefore, it is critical to develop sustainable management strategies for the control of bacterial wilt diseases, which can be strategically approached by screening resistant seeds, soil fumigation treatment with natural essential oils, chemical control, and microbial control. [9][10][11][12][13][14] Currently, the major strategy is still chemical control, involving applying agricultural bactericides (such as Thiessen copper, Zn thiazole, etc.) or essential oils with antibacterial active ingredients (such as phenols, terpenes, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…8 Therefore, it is critical to develop sustainable management strategies for the control of bacterial wilt diseases, which can be strategically approached by screening resistant seeds, soil fumigation treatment with natural essential oils, chemical control, and microbial control. [9][10][11][12][13][14] Currently, the major strategy is still chemical control, involving applying agricultural bactericides (such as Thiessen copper, Zn thiazole, etc.) or essential oils with antibacterial active ingredients (such as phenols, terpenes, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…For the curative effect (CE), first, the V. mali were inoculated and incubated for 48 h. Then, the prepared drug was evenly sprayed on the apple branches, and equal concentration of acetone was set as blank control. The PE and CE of compound 3f and fluconazole against V. mali were measured on apple tree branches with different concentrations (25,50, and 100 μg/mL). The PE and CE were calculated using formula 2.…”
Section: N T N Inhibition Rate (%) (mentioning
confidence: 99%
“…Effect of Compound 3f on Mycelial Morphology and Ultrastructure. According to the previous method, 25 the mycelium were treated with acetone and compound 3f (EC 50 value) as blank and treatment groups, respectively. Then, the mycelium was cultured at 25 °C on PDA medium for approximately 3 days, and the samples were prepared according to scanning and transmission EM.…”
Section: N T N Inhibition Rate (%) (mentioning
confidence: 99%
“…In order to explore the fungicidal mechanism of compound 76n , SEM and TEM observations and plasma membrane permeability were performed by Xu et al The results suggested that the R. solani hyphae treated with 76n were shriveled and folded and the organelles were partially blurred. Furthermore, compound 76n could apparently increase the cell membrane permeability.…”
Section: Fungicidal Mechanismmentioning
confidence: 99%
“…Using rosin as a precursor, Xu et al 80 designed and synthesized two series of rosin-based acylhydrazone compounds 75 and 76 and determined their antifungal activity. The bioassays indicated that all compounds 75a−75p showed weak antifungal activity, with inhibition rates between 1.4% and 34.9%.…”
Section: Structures and Activity Of Hydrazide Derivativesmentioning
confidence: 99%